The New Horizon of Antipsychotics beyond the Classic Dopaminergic Hypothesis-The Case of the Xanomeline-Trospium Combination: A Systematic Review - Octavian Vasiliu; Beatrice Budeanu; Mihai-Ștefan Cătănescu (MDPI AG, 2024)
Although the dopamine hypothesis of schizophrenia explains the effects of all the available antipsychotics in clinical use, there is an increasing need for developing new drugs for the treatment of the positive, negative, and cognitive symptoms of chronic psychoses. Xanomeline-trospium (KarXT) is a drug combination that is based on the essential role played by acetylcholine in the regulation of cognitive processes and the interactions between this neurotransmitter and other signaling pathways in the central nervous system, with a potential role in the onset of schizophrenia, Alzheimer's disease, and substance use disorders. A systematic literature review that included four electronic databases (PubMed, Cochrane, Clarivate/Web of Science, and Google Scholar) and the US National Library of Medicine database for clinical trials detected twenty-one sources referring to fourteen studies focused on KarXT, out of which only four have available results. Based on the results of these trials, the short-term efficacy and tolerability of xanomeline-trospium are good, but more data are needed before this drug combination may be recommended for clinical use. However, on a theoretical level, the exploration of KarXT is useful for increasing the interest of researchers in finding new, non-dopaminergic, antipsychotics that could be used either as monotherapy or as add-on drugs.